Sleeping Habits among Medical Students of King Edward Medical University, Associated Stress and Effects on Academic Performance - Tahir, Maliha; Haiy, Ata Ul; Tahir, Madiha; Kuraishi, Raafia Tafweez; Saqib, Sadia (Annals of King Edward Medical University, 2020)
Background: Inadequate sleep influences mental functioning, increases stress levels, and has a substantial impact on a student’s academic performance. Objectives: The study objective was to ascertain the sleeping habits among medical students of King EdwardMedical University, associated stress and effects on academic performance. Methods: This was a cross-sectional study conducted between May 2017 to July 2017 at King Edward Medical University, Lahore. It included a simple random sample of 227 medical students of the first and second years. A structured questionnaire formulated to assess the level of psychological stress, sleeping habits, academic performance, and demographic data was circulated among the students. Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality and Subjective Units of Distress Scale (SUDS) to assess psychological stress. Academic performance was equated to average marks obtained in the previous monthly tests. Chi-square test was performed to find an association of Sleep Quality with AcademicPerformance while Welch Test assessed the relationship between Sleep Quality and Psychological Stress. Results: 71.4% of students were found to have poor sleep quality with a mean sleep of 6 hours/night (SD ±1.636). 52.8% of students were having trouble staying awake during everyday activities. Poor sleep quality was standard for stressed students. No significant association was found between sleep quality and academic performance. Conclusion: We found a very high frequency of poor sleep quality among medical students, which was more common in stressed students. Sleep quality did not affect academic performance.